Pengembangan LKPD Berbasis Problem Based Learning pada Pembelajaran Tematik di Kelas V SD Negeri 28 Pontianak Selatan - Sri Rezeki; Kartono Kartono; Rio Pranata (Journal on Education, 2023)
Based on the results of the needs analysis in class V SD Negeri 28 Pontianak Selatan, learning in class V only uses thematic books so students become passive and students' critical thinking skills are low. Therefore, we need a learning tool that can make students active in learning as well as a learning model that can train students' critical thinking skills. The purpose of this study was to produce valid and practical Problem Based Learning worksheets for thematic learning in class V at State School 28 Pontianak Selatan. The research method used is Research & Development (R&D) to produce a new product, namely LKPD based on Problem Based Learning. The source of the data from this study were students in class V SD Neger 28 Pontianak Selatan and the data were questionnaire assessment scores from expert validators and students. The results showed that the LKPD Based on Problem Based Learning had an average value of 3.79 with a very valid category and the LKPD Based on Problem Based Learning had an average practicality value of 3.83 with a very practical category with a review of the assessment of language aspects, material, design, and practicality with a review of the trial results to students.